HISTORY OF THE ROMAN WORLD FROM A.D. 138 TO 337 - Parker, Henry Michael Denne. Link ([S.l.])
1 online resource
Keywords: A History of the Roman World from A.D. 138 to 337 (1958) looks at the last centuries of the Roman Empire, from the rule of Hadrian and his policy of consolidation of the Roman Empire, halting its further expansion, to the reign of Constantine and the rise of Christianity.